Why People Keep Coming Back to Religious Places: (a study on Wali Songo’s tomb in Java, Indonesia) - Ari Pranaditya; M. Iqbal Ramdhani; Faizzia Hidaya Kibria (Journal of Economics, Management, and Business, 2026)
The tourism sector is very important in the tourism business as it brings income to the government. As a subset of tourism, religious tourism has a lot of room to expand. The pilgrimage to Wali Songo is common in Indonesia, especially among certain Muslims. When a person makes a pilgrimage, the goal is to seek blessings (tabarruk) as well as mediate (tawassul) with the intermediary of blessings, scholars or guardians who are buried in the tomb to be visited, even though tabarruk and tawassul are indeed prohibited. The pilgrimage to the grave is not a form of command. However, it is an impermissibility exemplified by the Prophet Muhammad PBUH because not one evidence commands the pilgrimage to the grave to be carried out. However, the Wali Songo pilgrimage has a social, economic, and business significance in Indonesian religious tourism, making it a unique tourism destination for both visitors and locals. Revisit intention is the focus of this research. Apart from accounting for more than half of the total tourists in one tourist attraction for a specific purpose, it also has lower marketing costs than attracting first-time visitors.